2007
DOI: 10.1111/j.1365-2745.2007.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant functional types can predict decade‐scale changes in fire‐prone vegetation

Abstract: Summary1. Plant functional types (PFTs) are groups of species sharing traits that govern their mechanisms of response to environmental perturbations such as recurring fires, inundation, grazing, biological invasions and global climate change. The key components of a PFT approach are an underlying model of vegetation dynamics for a given system and a classification of functional types based on traits deduced from key processes in the model. 2. Prediction and generalization underpin the potential utility of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 46 publications
4
116
1
2
Order By: Relevance
“…The vegetation is fire-prone, with the herbaceous component regenerating rapidly and gradually becoming overtopped by shrubs within 5-6 years post-fire [33]. The soils, which derive from sandstone, tend to be highly infertile, acidic and silaceous.…”
Section: Methodsmentioning
confidence: 99%
“…The vegetation is fire-prone, with the herbaceous component regenerating rapidly and gradually becoming overtopped by shrubs within 5-6 years post-fire [33]. The soils, which derive from sandstone, tend to be highly infertile, acidic and silaceous.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that plant functional types responded predictably to changes in environmental conditions, such as soil resources or climate (e.g. Chapin et al 1996;Berry & Roderick 2002), but plant functional types determined in one ecosystem often failed when applied in other ecosystems (Keith et al 2007;Harrison et al 2010). Using plant functional traits to address this issue represents a more promising approach (Suding & Goldstein 2008;Ordonez et al 2009;Webb et al 2010), though predicting community functional composition via trait-based environmental filtering remains an important challenge (Lebrija-Trejos et al 2010;Laughlin et al 2011;Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If the trait shows responses to changes in environmental conditions it is called a response trait; the values or modality taken by a trait at a point of an environmental gradient is called an attribute (Violle et al 2007). A group of functional traits is called a plant functional type (PFT), but to be ecological meaningful each PFT should contain the most parsimonious number of traits only (as less traits as possible, but as much as needed; Keith et al 2007;Bernhardt-Römermann et al 2008). Using such PFTs we can estimate which functional trait composition is the result of differences in nitrogen availability on the estimated nitrogen gradient.…”
Section: Introductionmentioning
confidence: 99%